Pengaruh Pendidikan Madrasah Diniyah Terhadap Prestasi Belajar Mata Pelajaran Fiqih - Wardani, Dian Kusuma; Rahmawati, Maysarotu (JoEMS (Journal of Education and Management Studies), 2023)
The purpose of this study was to determine the effect of Madrasah diniyah education on Fiqh learning achievement in Class VII students at Madrasah Tsanawiyah PPAI Darun Najah Ngijo Karangploso Malang. This type of research is quantitative research with statistical analysis methods, namely one sample t test. The objects in this research are students who are involved in learning in Madrasah Diniyah and learning Fiqh Subjects. Secondary data is data used in research that takes from existing sources. One sample t test is used to determine the effect of a treatment. Based on the results of the analysis using a one-sample t-test, the results obtained a significant value of 0.000 < alpha (0.05) this indicates that there is an influence of Madrasah Diniyah education on Fiqh learning achievement in class VII students of Madrasah Tsanawiyah PPAI Darun Najah Ngijo Karangploso Malang.